TRANSFORMING OF EDUCATION IN THE ERA OF AL: BETWEEN ETHICS, TECHNOLOGY, AND GLOBAL COMPETENCE - Harahap, Enita Oktavia; Pratama, Winda Wahyu; Widyatmoko, Kustanto; Azzahra, Fatmi (MSJ : Majority Science Journal, 2025)
Abstract The development of Artificial Intelligence (AI) has had a significant impact on the world of education, encompassing teaching methods, curriculum design, and evaluation systems. This study aims to analyze the transformation of education in the AI ​​era by emphasizing the interrelationships between ethical aspects, technology utilization, and strengthening global competencies. The research method uses a descriptive qualitative approach through a literature review sourced from scientific journals, policy documents, and relevant international reports. The results show that AI plays a strategic role in enhancing personalized learning, providing a more efficient evaluation system, and expanding access to education, particularly in remote areas. However, its implementation also presents ethical challenges, such as data privacy issues, potential algorithm bias, and the risk of unequal access due to the digital divide. In facing these dynamics, the younger generation is required to master global competencies, including digital literacy, critical thinking skills, cross-cultural communication, and collaborative skills to adapt to the rapid changes in the digital era. This study confirms that AI-based educational transformation can only be optimal if there is a balanced integration of technology, ethics, and global competencies in the curriculum, as well as the support of adaptive, inclusive, and sustainable national policies, especially in developing countries.